2016
DOI: 10.1111/gcb.13480
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic N deposition increases soil organic matter accumulation without altering its biochemical composition

Abstract: Accumulating evidence indicates that future rates of atmospheric N deposition have the potential to increase soil C storage by reducing the decay of plant litter and soil organic matter (SOM). Although the microbial mechanism underlying this response is not well understood, a decline in decay could alter the amount, as well as biochemical composition of SOM. Here, we used size-density fractionation and solid-state C-NMR spectroscopy to explore the extent to which declines in microbial decay in a long-term (ca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 60 publications
(91 reference statements)
4
80
0
Order By: Relevance
“…4). This idea is also supported by a recent study that showed the identical biochemical composition of mineral soil organic matter between ambient and elevated N plots in a temperate forest (Zak et al, 2017). However, given that the chemical fractionation method used in the present study (Wang et al, 1998) was unable to isolate pure specific compounds, whether or not the inhibition of SOC decomposition by N addition is different among specific biochemical compounds should be further investigated.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…4). This idea is also supported by a recent study that showed the identical biochemical composition of mineral soil organic matter between ambient and elevated N plots in a temperate forest (Zak et al, 2017). However, given that the chemical fractionation method used in the present study (Wang et al, 1998) was unable to isolate pure specific compounds, whether or not the inhibition of SOC decomposition by N addition is different among specific biochemical compounds should be further investigated.…”
Section: Discussionsupporting
confidence: 76%
“…S2). Potential mechanims have been proposed to explain the N inhibition of SOC decomposition in aggregate-occluded and mineral-associated fractions (Neff et al, 2002;Cusack et al, 2011;Riggs et al, 2015;Zak et al, 2017). For example, N addition may alter decomposition of aggregate-occluded SOC through reducing carbon allocation to aggregate-binding agents such as fine roots and fungal hyphae (Li et al, 2015), and may inhibit decomposition of mineral-associcated SOC via acidifyiing soils and increasing mineral surface reactivity (Tian and Niu, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under European conditions with N depositions ranging from 20 to > 100 kg per ha and year, the question of increased N deposition and humus formation should also be addressed. N deposition have the potential to increase soil C storage (Zak et al, 2017). The explanation of organic matter accumulation in polluted soils was first searched in the impact of pollutants on microbial communities (Sterritt and Lester, 1980) but later studies showed that earthworm communities were strongly impacted by soil pollutants (Nahmani and Rossi, 2003), resulting in pronounced changes in soil structure and burying of litter.…”
Section: Humus Systems and Global Challenges In The Anthropocenementioning
confidence: 99%